P246 Should we Telephone Missed Asthma Appointments? A Follow-Up Evaluation of Four Years of Practice. (12th November 2015) - Narang, Y; McDonough, B; Ahmad, M; Mault, S; Dillon, C; Burhan, H; Beveridge, NER
Abstract : Introduction: We have previously shown that telephone contact following missed asthma clinic appointments is a resource-intensive method of improving compliance in a relatively small group of patients. 1 Poor adherence to treatment leads to increased admissions and reduced quality of life. Reducing rates of missed appointments is a key efficiency target for service delivery for the hospital. Aim: To evaluate the outcome of telephone contact following missed asthma clinic appointments in a larger data set. Methods: We reviewed the outcomes of telephone contact with patients following a missed appointment at a difficult asthma clinic at an inner city hospital between 2011 and 2014. Difficult asthma is defined as ongoing symptoms despite level 4–5 treatment. Successful contact was defined as speaking to the patient or receiving a message. Unsuccessful contact describes when messages were left for patents but no response achieved. Results: Between 2012 and 2014 (inclusive) 457 patients missed an appointment. We attempted to contact 324 patients. Successful contact was made with 112 patients; 50 then attended clinic. Contact was unsuccessful for 212 patients; 59 then attended clinic. Due to a lack of contact details, no contact was attempted in 133 patients; 31 then attended clinic subsequently. The relative increase in clinic attendance following contact was 1.95 when compared to the no contact group, and 1.6 compared to the unsuccessful contact group. Unsuccessful contact produced a relative increase of 1.2 compared to no attempted contact. Conclusion: Telephoning patients following a missed asthma clinic appointment is relatively resource intensive method of doubling clinic attendance. In the unsuccessful contact group, telephone calls were frequently not answered or were voicemail messages were not responded to. Yet there does appear to be a small benefit in attendance rates in this group compared to the no contact group. Because the groups were not randomised confounding factors may be present. Services that provide prospective reminders and perhaps use a free text service may be more effective and less labour intensive. Reference: 1 McDonough B, Mault S. Non-attendance at a difficult asthma clinic. Nursing Times 2013;109 (16):2–14